MEHP/ethanol co-exposure favors the death of steatotic hepatocytes, possibly through CYP4A and ADH involvement. (December 2020) - Tête, Arnaud; Gallais, Isabelle; Imran, Muhammad; Legoff, Louis; Martin-Chouly, Corinne; Sparfel, Lydie; Bescher, Maëlle; Sergent, Odile; Podechard, Normand; Lagadic-Gossmann, Dominique
Abstract: Liver steatosis has been associated with various etiological factors (obesity, alcohol, environmental contaminants). How those factors work together to induce steatosis progression is still scarcely evaluated. Here, we tested whether phthalates could potentiate death of steatotic hepatocytes when combined with ethanol. Pre-steatotic WIF-B9 hepatocytes were co-exposed to mono (2-ethylhexyl) (MEHP, 500 nM; main metabolite of di (2-ethylhexyl) phthalate or DEHP) and ethanol (5 mM) for 5 days. An increased apoptotic death was detected, involving a DNA damage response. Using 4-Methypyrazole to inhibit ethanol metabolism, and CH-223191 to antagonize the AhR receptor, we found that an AhR-dependent increase in alcohol dehydrogenase (ADH) activity was essential for cell death upon MEHP/ethanol co-exposure. Toxicity was also prevented by HET0016 to inhibit the cytochrome P450 4A (CYP4A). Using the antioxidant thiourea, a role for oxidative stress was uncovered, notably triggering DNA damage. Finally, co-exposing the in vivo steatosis model of high fat diet (HFD)-zebrafish larvae to DEHP (2.56 nM)/ethanol (43 mM), induced the pathological progression of liver steatosis alongside an increased Cyp4t8 (human CYP4A homolog) mRNA expression. Altogether, these results further emphasized the deleterious impact of co-exposures to ethanol/environmental pollutant towards steatosis pathological progression, and unraveled a key role for ADH and CYP4A in such effects. Graphical abstract: Image 1 Highlights: MEHP/EtOH co-exposure leads to death of steatotic hepatocytes via oxidative DNA damage. MEHP-activated AhR would enhance ethanol metabolism by ADH in steatotic cells. The toxicity by MEHP/EtOH co-exposure would rely on CYP4A activity in steatotic cells. Co-exposure to DEHP/EtOH of HFD-zebrafish larva induces progression of liver steatosis.